Analysis of studentsâ science motivation and nature of science comprehension in middle school - Wicaksono, Azizul Ghofar Candra; Minarti, Ipah Budi; Roshayanti, Fenny (University of Muhammadiyah Malang, 2018)
The purpose of this study was to explore the pattern of science motivation and nature of science (NoS) and the relationship between science motivation and nature of science in middle school students located in Semarang, Central Java, Indonesia. The design of this study was survey followed by the correlation study to discover the relationship between science motivation level and nature of science comprehension. This research included 113 students as sample. The instrument used for data collection was SMQ and seven essay test from NoS indicator. This study revealed that the students had a median score of science motivation and the low score in nature of science comprehension. There were studentsâ science motivation and nature of science comprehension urgently need to be improved. It can be done by developing learning process and any support from school or family.